Recycling of fresh concrete slurry waste as supplementary cementing material: Characterization, application and leaching of selected elements. (20th September 2021) - Keppert, Martin; Davidová, Vendula; Doušová, Barbora; Scheinherrová, Lenka; Reiterman, Pavel
Highlights: Fresh Concrete slurry waste on-site recycling as Supplementary Cementing Material. Thorough characterization of Concrete slurry waste. 10% cement replacement by recycled Concrete slurry waste. CSW recycling did not worsen the leaching of selected elements from concrete. Abstract: Concrete slurry waste (CSW) is generated in ready-mix and precast concrete plants after the reclaiming of aggregates from unused concrete. CSW contains hydration residuals (portlandite, calcite, C-S-H and hydrated aluminate phases), as well as fine particles of aggregates. The amount of CSW produced in a ready-mix plant is about 0.8% of produced concrete, thus it is huge amount of material to be treated. Several recycling strategies of CSW have been proposed; most of them are based on the high content of portlandite and calcite. Nevertheless from the point of view of the ready-mix plant, the preferred way is on site recycling – as a component of produced concrete. The present paper aims to evaluate possible utilization of CSW in the role of Supplementary Cementing Material (SCM). CSW is not a conventional reactive additive such as e.g. fly ash, but it is very fine and contains a certain amount of residual clinker minerals and high amount of calcite, which is used successfully as SCM. The CSW under study was collected as a fresh material after aggregates reclaiming, partially dewatered and immediately used as the cement replacement in concrete. The 10% dosing did not cause any decrease of strength; the applicability of CSW in a higher amount was limited by its high fineness, which reduced the workability of the mixture. The CSW itself has been distinguished by elevated chromium leaching; the incorporation of CSW in concrete caused Cr immobilization. The performed experiments demonstrated that the on-site recycling of the fresh CSW as a concrete component is feasible.